Islamic Economic Development: A Selected Literature Review - Handoko, Luqman Hakim; Nurlia, Nurlia (Universitas Muhammadiyah Pontianak, 2023)
The study on the concept and philosophy of Economic development in Islamic perspective are quite rare. There is gap between the concept and the current research that tend to on quantitative. Therefore, this study aims to investigate the literature on Economic development in Islamic perspective. this study used content analysis where the data retrieved from google scholar. The study found that the meaning and the concept of economic development are relatively similar to each other. May they differ in attention, some in detail, and some in general explanations. Interestingly, there are some studies, in the past scholars, who give attention to economic development. Interestingly, earlier scholars such as al-Mawardi, Ibn Khaldun and Shah Waliyullah has already elucidated widely on this matter. Their theory and explanation are some similar to the contemporary theory and some more comprehensive.